Updated generalized natural gas reciprocating engine part-load performance curves for cogeneration applications. (3rd October 2017) - Zakrzewski, Thomas; Stephens, Brent
Abstract : The efficiency of combined heat and power systems, which most commonly utilize natural gas reciprocating engines, is strongly influenced by the performance of generation sets at part-load conditions. However, there is currently a lack of comprehensive data on the part-load performance of generation sets, which can lead to model inaccuracies when evaluating combined heat and power systems early in the design phase. The current work reviews recent manufacturer reports and several industry publications to summarize the part-load thermal and electric performance of 67 natural gas spark ignition reciprocating engines from a wide variety of manufacturers and nominal capacity ranges that are commonly used in combined heat and power applications. Comparisons between linear and nonlinear performance curves for part-load heat-to-power ratios and electric heat rates demonstrated that, for most cases, nonlinear Power Law functions more accurately characterize performance above 50% part-load. The data were also used to develop a set of generalized nonlinear performance curves that extend below 50% part-load ratio that are intended for engineers to use in evaluating combined heat and power systems when more detailed performance data is not available.